Generation Z and Spiritual Maturity. Issue 1 (April 2020) - Bergler, Thomas E.
Those wanting to form members of Generation Z into mature disciples must overcome the challenges presented by their shared generational traits. This article summarizes the biblical teaching on spiritual maturity, documents a division within Generation Z between "engaged" and "churched" Christians, synthesizes current research on Generation Z to identify traits that could hinder discipleship efforts, and uses the biblical traits of spiritual maturity to offer guidance in addressing those challenges.